Lean Kōhai meditations for strategy, practice, and balance in living change management. - Arp, Don. ([S.l.] : PRODUCTIVITY PRESS, 2025)
This book consists of 76 statements on various issues and practices encountered by process improvement/operational excellence (PIOpEx) practitioners, managers, and leaders. Many of these issues are also encountered by those outside of PIOpEx. This book contains instructions, encouraging readers to write and journal in its pages. The key benefits of this work fuel the unending learning journey of PIOpEx practitioners and leaders. Practitioners face issues regarding practice, methods, leadership, management, and purpose. The reflections in this book allow them to either tackle the issue upfront and be prepared or the reflections can act as jump-off points to develop an approach to an issue encountered, individually or as a team. For example, the practitioner may have a problematic team member, and using a reflection from the book and having the group discuss it may resolve the issue. Or, the practitioner can read a reflection and use their response to develop a strategy for handling the team member. Essentially, this book provides readings that could form the basis of daily meditation, be consulted for perspective when a specific issue arises, or both. It seeks to instill a mindset of emotional intelligence that can then fuel the pursuit of meaningful, lasting change.
Keywords: Performance -- Evaluation; Organizational change; BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Strategic Planning